Medallion Relief as A Source of Ideas for Creating Artworks Utilising Wood Waste - Tri Yuliana; Vina Meilinda; Fauziah Dwi Rohmawati (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2025)
The concept of local culture and environmentalism is a genre of art and art practice that seeks to introduce, maintain, preserve and revive the love of culture and the environment. This is because in recent times local culture has been displaced by modernisation, and the love for the environment has declined. So that an effort is needed to regenerate the love of local culture and the environment. The purpose of this research is to create artworks with the theme of local culture and environment-based, namely medallion reliefs and wood waste. Artworks with the theme of local culture and waste utilisation are one of the efforts to introduce, maintain and preserve local culture and the environment through art. The research method uses Arts based Research which is an arts-based research with the principle of adapting art creativity to social research with an artistic practice approach, because both are holistic and dynamic involving reflection, description, problem formulation and problem solving, as well as the ability to identify and explain intuition and creativity in the research process. Artistic practice uses a three-stage experimental sequence, namely: exploration stage, design stage, and realisation stage. The results of this research show that wood waste has high potential to be utilised as an alternative medium for art creation. The result of this creative process is a medallion-themed collage artwork that is environmentally friendly and affordable.